If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(1.5) = 2772 Multiply 3 * 1.5 2x + 4.5 = 2772 Reorder the terms: 4.5 + 2x = 2772 Solving 4.5 + 2x = 2772 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4.5' to each side of the equation. 4.5 + -4.5 + 2x = 2772 + -4.5 Combine like terms: 4.5 + -4.5 = 0.0 0.0 + 2x = 2772 + -4.5 2x = 2772 + -4.5 Combine like terms: 2772 + -4.5 = 2767.5 2x = 2767.5 Divide each side by '2'. x = 1383.75 Simplifying x = 1383.75
| 5(y-1)=6(y-5) | | 1/3x-6=4+2x | | 9+8x=93 | | 4=7v-8/8+v-6/4 | | 4b-6-12b-4= | | 2x+3y=2772 | | x-25=5+11x | | K=-5/2 | | 3y-(-4y+3)=-17 | | (x-2)/6=(x+3)/9 | | 35-8x=22 | | 7(6+2)= | | -(5a+4)+1=2-(5a-1) | | -22.4+6x=75.5 | | t/-17.7=-12.7 | | -(2a-2)+3=3-(2a+5) | | 6(3-2)x=54 | | 5(a+4)-(4a+4)=4(5a-2)+5 | | 900=x-.5 | | 7(2y+7)+(-36y)= | | 6x^5-4x^2+10x=0 | | -6n-1n=16 | | x^8-2x=0 | | 8(-16)/2(-8)-5(-3) | | 4-4(2a-3)=0 | | 6-3|-8r-9|=-15 | | (2x-1)/(9-x^2) | | -3|9m+2|+10=10 | | y^1/6(y^11/6+y^23/6) | | log(x+1)+2*log(x)=log(x^2+8) | | 4-9|-6-b|=-14 | | 10-10|-8k+4|=40 |